1965
DOI: 10.1104/pp.40.4.725
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast damage due to enzymatic hydrolysis of endogenous lipids.

Abstract: lageindorf and Evanis (15) reported that the rates of 2, 3', 6-trichlorophenolindophenol (TCPIP)5 reduction by chloroplasts isolated from the primary leaves of red kidney bean are strongly dependent uI)on the pH of the buffer in which the leaves are homogenized. Grindiing leaves at pH values below 8 resulted in chloroplasts whose Hill reaction was rapidly and irreversibly inhibited. In contrast, the chloroplasts of sonie plants, including those from spinach, are not inactivated under these conditions. Clenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
0
1

Year Published

1968
1968
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 25 publications
(15 reference statements)
2
56
0
1
Order By: Relevance
“…It has been shown that incorporation of UDP-Gal into MGDG is gradually decreased, but incorporation into oligogalactolipids is steadily increased or accelerated when chloroplasts (9,19) and envelopes (5) are incubated for prolonged periods. This observation may be partly accounted for by the inhibition of UDGT and the stimulation of GGGT activity by FFA, since FFA is known to be readily produced by aging of chloroplasts (13,17,22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that incorporation of UDP-Gal into MGDG is gradually decreased, but incorporation into oligogalactolipids is steadily increased or accelerated when chloroplasts (9,19) and envelopes (5) are incubated for prolonged periods. This observation may be partly accounted for by the inhibition of UDGT and the stimulation of GGGT activity by FFA, since FFA is known to be readily produced by aging of chloroplasts (13,17,22).…”
Section: Discussionmentioning
confidence: 99%
“…Lipases with pH optima of 5.6 for the hydroalysis of uinsatulrated digalactosyild.glvcerides andl 7.0 for the hydrolysis of tnsaturated monogalactosyl,diglycerides were foulnd in runner beans by Sastry and Kates (14). A small galactolipid lipase activity was foulnd at pH 7.0 in spinach (10).…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitory effect on the Hilll relaction by unsatturated fatty acids had been found by Krogmann and Jagendorf (8) and more recently by McCairty and Jagendorf (10) and Molotkovfsky and Zheskova (11). Therefore, it seemed thait an analysis of the free fatty acids of ch'loroplasts might indicate the reason for the loss of Hill activity during a!ging of Ohloroplasts.…”
mentioning
confidence: 94%
“…The release of fatty acids during aging processes in vitro has been demonstrated in several cells and organelles such as human erythrocytes (30), mitochondria (10) and chloroplasts (8,16,22,39,41). In chloroplasts, the main fatty acids released in the course of aging are Cis-unsaturated fatty acids (8,16,39), particularly linolenic acid; these acids are the most abundant in the thylakoid (8,39) and envelope (21) membrane lipids.…”
mentioning
confidence: 99%
“…A hypothesis explaining the inhibition of photosynthesis by linolenate is presented. Key words: Chloroplasts -Linolenic acid treatment -3-P-glyceraldehyde effluxPhosphate uptake -Photosynthesis -Spinach -Transport.The release of fatty acids during aging processes in vitro has been demonstrated in several cells and organelles such as human erythrocytes (30), mitochondria (10) and chloroplasts (8,16,22,39,41). In chloroplasts, the main fatty acids released in the course of aging are Cis-unsaturated fatty acids (8,16,39), particularly linolenic acid; these acids are the most abundant in the thylakoid (8, 39) and envelope (21) membrane lipids.…”
mentioning
confidence: 99%